A report of 49 cases of cnidarian envenoming from southeastern Brazilian coastal waters - Haddad, V; da Silveira, F. L.; Cardoso, JLC; Morandini, A. C. (Elsevier B.V., 2002)
Forty-nine accidents caused by jellyfish (Cnidaria) were observed during a period of 5 years on the southeastern coast of Brazil. Most of them involved male patients (65.3%), the injured areas being mainly the legs (71.3%) and the trunk (65.3%). Twenty accidents with Chiropsalmus quadrumanus, four with Physalia physalis and 20 with unidentified jellyfish presented intense pain, linear plaques and systemic symptoms. The five cases with Olindias sambaquiensis caused mild pain, round plaques and no systemic symptoms. There are a few reports on accidents caused by jellyfish, in this country, and scarce clinical or epidemiological data are available up to the present moment. (C) 2002 Elsevier B.V. Ltd. All rights reserved.
Keywords: Brazil; jellyfish; Cnidarians; stings; venomous marine animals